Pengembangan Sepeda Listrik Bertenaga Surya Sebagai Transportasi Ramah Lingkungan - Fakhrurozi, A. Shodiq; Basuki; Anisa Rokhmahwati, Dian; Satriya Hadi, Fajar (UNHASY, 2022)
Electric bicycles are alternative fuel vehicles. Electric bicycles use an energy source in the form of electricity. Many alternative energy potentials can be developed in Indonesia, including solar power. To be able to convert solar energy into electricity, a solar panel is needed. The problem in this study is how the design process and performance efficiency of solar electric bicycles are, while the purpose of this study is to determine the design process and performance efficiency of solar electric bicycles. The type of research used by the author is a research and development method. The test is carried out after the manufacturing process is complete, starting from the manufacture of the solar panel holder, the buffer holder, the dynamo holder, and the assembly of the electrical components. The test was conducted to determine the speed and a distance of 700 meters with a user weight of 61Kg. From the results, it was found that to be able to travel a distance of 700 meters took an average of 2 minutes 27 seconds with an average speed of 18 kilometers/hour.